2013
DOI: 10.1111/1471-0307.12047
|View full text |Cite
|
Sign up to set email alerts
|

The physicochemical properties of yoghurt supplemented with microencapsulated peanut sprout extract, a possible functional ingredient

Abstract: This study was designed to determine the physicochemical and sensory properties of yoghurt supplemented with powdered peanut sprout extract microcapsules (PPSEM) (3–10 μm) during storage at 4 °C for 16 days. The releasing rates of the polyphenol, resveratrol, from yoghurts were minimised at lower concentrations of PPSEM (0.25 and 0.5%, w/v). The viscosity decreased gradually with higher concentrations of PPSEM added. In the sensory test, there were significant increases in yellowness, peanut and cooked scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 26 publications
0
10
1
1
Order By: Relevance
“…pH and acidity of yogurt during storage There was no significant difference between the pH values of fortified and control yogurt samples at each analysis times and the pH of both samples did not decrease significantly during the storage time (Table 1). This is in contrast to Lee et al (2013) and Tamjidi et al (2012) who reported that the pH values of yogurt samples with or without microencapsulated bioactive compounds decreased during storage time. Also, acidity values of both samples did not change significantly during the storage time.…”
Section: Stability Of Entrapped Thymoquinone In Microencapsulated N contrasting
confidence: 95%
See 1 more Smart Citation
“…pH and acidity of yogurt during storage There was no significant difference between the pH values of fortified and control yogurt samples at each analysis times and the pH of both samples did not decrease significantly during the storage time (Table 1). This is in contrast to Lee et al (2013) and Tamjidi et al (2012) who reported that the pH values of yogurt samples with or without microencapsulated bioactive compounds decreased during storage time. Also, acidity values of both samples did not change significantly during the storage time.…”
Section: Stability Of Entrapped Thymoquinone In Microencapsulated N contrasting
confidence: 95%
“…This is in contrast to Lee et al . () and Tamjidi et al . () who reported that the pH values of yogurt samples with or without microencapsulated bioactive compounds decreased during storage time.…”
Section: Resultsmentioning
confidence: 89%
“…Peanut sprouts due to its health promoting properties such as anti‐obesity, antioxidant, and anti‐arthritic, and laxative have been contributed to the prevention of diseases (Ahn et al ., ; Choi et al ., ; Kim et al ., , ; Seo et al ., ; Chang et al ., ; Kang et al ., ). For the multifunction of peanut sprout, people added its powder in dairy product or made peanut sprout extract microencapsulation (Ahn et al ., ; Lee et al ., ,b). However, there are quite few researches on the resveratrol accumulation during the germinating procedure of peanuts.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al also studied physicochemical properties of yoghurt supplemented with microencapsulated peanut sprout extract and its properties during storage. They concluded that the low concentrations (0.25 and 0.50%, w/v) could be used to produce powdered peanut sprout extract microcapsules (PPSEM)-supplemented yoghurt without significant adverse effects on the physicochemical and functional properties (Lee et al, 2013c). Meanwhile, the low concentrations of the microcapsules (0.5 and 1.0%, w/v) could be suitable to produce the microcapsule-supplemented milk without significant adverse effects on the physicochemical and sensory properties of milk (Lee et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%